(untitled) (Research, Society and Development, 2021)
Education is one of the enablers for citizens to enter the job market. However, in order to democratize the access of all to a quality and inclusive education, the methods must be adjusted so that deaf people, who are the target of the present study. The research sought to investigate the use of the assistive technology VLibras, which involves a set of videos in Brazilian Sign Language (LIBRAS) for deaf people. With the use of VLibras, it is possible to add the LIBRAS translator to the video classes with little video editing effort. Based on descriptive qualitative methods, a bibliographic survey was carried out. The results show there is evidence that assistive technologies contribute to the autonomy of students with special needs. And that the VLibras software is a viable option in the construction of video classes, however the need for the teacher to perform video editing with editing software.